Art and urban space in Athens: The spatial composition of a street art paradise - Karanicolas, Johnny (The Australian journal of anthropology, 2025)
This paper explores how Athens's urban spaces, shaped by historical processes of rapid growth, unplanned development, and urban decay, have actively fostered a vibrant street art scene and related subversive practices during Greece's economic crisis. Based on ethnographic fieldwork (2015–2019) in central neighbourhoods like Exarchia and Psirri, it argues that the city's irregular urban landscape and contested public spaces empower heterotopic practices such as street art, squatting, and grassroots activism. Framed by Lefebvre's spatial triad and Foucault's heterotopia, urban space emerges as an active agent in shaping social resistance against homogenising forces. Amid the socioeconomic turmoil of the crisis, Athens became a ‘graffiti paradise’, where artists and collectives reclaimed derelict spaces, challenged gentrification and resisted control. Ultimately, the paper illustrates how urban space and social action intertwine to produce a dynamic, resilient, and anti-institutional art scene on Europe's periphery, highlighting the role of urban space as a social agent.